STUDIES ON ROOTING PATTERN OF ACID LIME BY ROOT EXCAVATION - SINGH, BALBIR; CHANDRA, ATUL (Annals of Agricultural Research, 2014)
Distribution of roots at different distances from the tree trunk viz. 0-60 cm, 60-120 cm and 120-180 cm and soil depths viz. 0-25 cm, 25-50 cm and 50-75 cm were studied using the root excavation method in seven years old acid lime. The root distribution pattern is influenced by the distance from tree trunk, the soil depth and the season of excavation. It was observed that root density was found maximum at nearest radial distance from tree trunk i.e. 0-60 cm. (86.07 per cent and 62.46 per cent during post rainy and spring season, respectively) and an increase in distance from the tree trunk resulted in reduction of root density considerably. During post rainy season, roots were maximum at 0 to 25 cm, followed by 50 to 75 cm and 25 to 50 cm soil depths. During the spring season, the quantity of roots decreased with an increase in soil depth. Root density was higher during the postrainy season than in spring at different distances from the tree trunk. Feeder roots (< 0.2 cm indiameter) and medium (> 0.5 - 1.5 cm in diameter) roots were maximum as compared to thin (> 0.2- 0.5 cm in diameter) and thick (> 1.5 cm in diameter) roots in acid lime.